IC 9433 Backfilling Materials And Methods For Stress Transfer Modification In Deep Longwall Coal Mines - Charles V. Jude (The National Institute for Occupational Safety and Health (NIOSH), 1995)
This U.S. Bureau of Mines report presents a review and evaluation of existing and new backfilling materials and methods for their applicability to the problem of gate road stress reduction in deep retreat longwall coal mines. Candidate backfill materials include pulverized coal combustion fly ash, flue gas desulfurization, and fluidized bed combustion by-products from coal-fired electric power generation plants. Properties of both backfill and its component materials are presented, with particular emphasis on the unconfined compressive strength and elastic modulus of backfill mixtures. Hydraulic mix designs discussed in this report include high-water content slurry and low-water content paste fills. Three gate road stress-transfer-modification concepts are proposed to reduce abutment stresses in gate road systems. The first concept, packwalling, involves packwall construction behind the headgate shield inby the face and adjacent to the headgate pillars. The second concept, gob-filling, involves infilling a strip of gob inset from and parallel to the headgate using paste injection methods patterned after a technology recently developed in Europe. In the third concept, entry-filling, slurry fill methods are used to fill abandoned gate roads and crosscut entries inby the face.